The Viewpoint on Legislation and Guidelines on e-Business and e-Commerce: Kazakhstan’s Approac - ISMAILOVA, Bakytgul; KURMANOVA, Aigul; ALIMPIYEVA, Tatyana; BALABIYEV, Kairat; ALTYNBEKKYZY, Alua; ALTYNBEKULY, Aidar (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).19, 2020)
According to Global Information Technology Report, Kazakhstan ranks 39th among countries actively introducing information technologies into electronic business and electronic commerce. The legislative development for e-business and e-commerce in Kazakhstan has begun since 1999, a number of legislative regulations and guidelines have been developed by national parliament of Kazakhstan. The purpose of this article is to present and analyze viewpoint on current national legislation and guidelines on e-business and e-commerce in post-soviet Kazakhstan. This article uses comparative method of legal rules governing e-business and e-commerce issues between Kazakhstan and international countries. Furthermore, it applies a system method, where e-business and e-commerce was considered as a co-economic-legal phenomenon in the mutually agreed existence of its main components such as e-document circulation and e-economy. The article concludes that there is no clearly nationally formulated concept of legal regulation of e-business and e-commerce, there is no clear terminology base and uniform usage of terms, a clear idea of how and what should be regulated. The article highlights that Kazakhstan needs to apply integrated approach with further revision of national legislation and guidelines considering experiences of developed countries and standards of the United Nations convention on the use of electronic communications in international contracts.   This review article explores a problematic area of national legislation and guidelines on e-business and e-commerce in transitional Kazakhstan which display interests to e-business and e-commerce and at the same time, country experiences the difficult economic situation, caused by decreasing oil prices, higher inflation and significant devaluation of the national currency.